The Pelanduk Jenaka’s character strategies in the power creation and sovereignty in Hikayat Pelanduk Jenaka - N. S. A., Rahman; S. J .N., Muhammad (ASR Research India, 2022)
Children's reading materials such as animal stories are suitable for use as entertainment and teaching materials that can educate children. In this regard, the stories featured in animal stories are capable of stimulating the child's mind and are able to shape their personality, personality, thought patterns and emotions. The exposure of natural elements such as small-conscious fauna can bring the animal's life closer to life. The characters of the animal story can provide the best example and teaching for an ageing child. This story of such a delicate and light animal can facilitate the reading and understanding of children. Through this study, children can be exposed to characters such as the smart and Pelanduk Jenaka in expanding their power and sovereignty. Although, the Pelanduk Jenaka is a small-sized animal, but its ingenuity is able to conquer the animals in the jungle. Hence, this study will analyze some of the strategies used by the Pelanduk Jenaka in creating its power and sovereignty. The study will use the Hikayat Pelanduk Jenaka as a study data. The results showed that startegies such as changing self-skills and influencing thinking and behavior were able to strengthen the position of the King and be certified as a leader in the jungle. Therefore, children who read the story of this animal can make this story an example and a lesson as well as be able to think good and bad of a situation and be applied in their lives with a good purpose.